Influence of geometry on the dynamic behaviour of steel tubular towers for onshore wind turbines - Folster, Kaylee (Department of Civil Engineering, 2017)
South Africa has recently experienced challenges regarding electricity consumption and availability. As part of the country's Integrated Resource Plan, these challenges are to be addressed. This involves a 20 year plan which aims to increase electricity supply capacity as well as reduce the reliance on coal power as part of the global trend to become more environmentally friendly. Wind power, specifically, is to account for a large portion of the renewable energy that is expected to become available by 2030. This results in the need for the understanding of wind turbine design by South African engineers. The dynamic analysis of wind turbine structures, is of particular interest to Civil Engineers. Wind turbine towers are recently of the monopole or tubular type tower, predominantly constructed of either concrete or steel or a combination of both. Steel tubular towers above a height of 80m are generally not recommended for wind turbines owing to cost concerns as well as difficulties in meeting dynamic behaviour requirements. Concrete towers and steel-concrete hybrid towers are recommended for this height regime. The aim of this study was to assess the prospective use of steel tubular towers of varying geometric shape for wind turbines with tower heights of 80m or greater. The study focussed on the analysis of natural frequency and assessing the applicability of steel tubular towers of geometric shapes that have not been previously explored or reported. The turbine of choice for this study was the Vestas V112 3MW type as this is one of the most commonly used and more efficient turbines for towers of this height regime. The results of this study showed that steel monopole towers of heights of 80m and more are still viable options for wind turbine towers. Various geometric tower cases of heights varying from 80m to 120m, produced acceptable fundamental natural frequencies within the allowable frequency range for a Vestas V112 3MW turbine.